2012
DOI: 10.1093/ejcts/ezs524
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of infection in paediatric veno-arterial cardiac extracorporeal membrane oxygenation: role of procalcitonin and C-reactive protein

Abstract: Neither PCT nor CRP are reliable markers of infection in paediatric cardiac ECMO patients. However, high levels of PCT are associated with MODS. PCT may be used as a prognostic indicator of clinical outcome in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…ECMO in the pediatric population has become standard of care not only for short-term bridge to recovery (9), to other bridging devices, and to transplantation, but also as bridge to repair (10), to therapy (11), and finally as a bridge to diagnosis, in selected cases (12). Indications have expanded considerably through the years, including support for respiratory distress syndrome, multisystem organ failure, burns, traumatic hemorrhage, sepsis, myocarditis, malignant arrhythmias, and circulatory support after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ECMO in the pediatric population has become standard of care not only for short-term bridge to recovery (9), to other bridging devices, and to transplantation, but also as bridge to repair (10), to therapy (11), and finally as a bridge to diagnosis, in selected cases (12). Indications have expanded considerably through the years, including support for respiratory distress syndrome, multisystem organ failure, burns, traumatic hemorrhage, sepsis, myocarditis, malignant arrhythmias, and circulatory support after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates, especially of low body weight, and young infants are uniquely vulnerable to ECMO-related complications, including neurologic injury, hemolysis, hyperbilirubinemia, hypertension, renal failure, and sustained systemic inflammatory response syndrome (5)(6)(7)(8). In turn, the lower priming volumes and lesser prosthetic surfaceblood interaction hold the potential for reduced inflammatory response (9,15). Factors that may exacerbate these complications include the type of the pump itself (7,8,13), duration of support, components of the circuit, particularly the oxygenator, and exposure of red blood cells to sheer stress generated by the high negative or positive pressure (6), the surface of the tube circuit, and, possibly, nonphysiological conditions, such as the continuous, nonpulsatile flow (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP is also elevated to levels seen with infection, whereas PCT is not. CRP did not correlate with clinical outcomes [21]. They found that children with SIRS associated with bacteria had similar PCT levels to patients with noninfectious SIRS on postoperative day 1, but the PCT levels were higher on postoperative days 2 and 3 in those patients with infectious SIRS [20].…”
Section: Determining the Presence Or Absence Of Infection In Febrile mentioning
confidence: 99%
“…Because of the reversibility of the ventricular dysfunction observed during fulminant myocarditis in some patients and the option of cardiac transplantation, for those whose ventricular function does not recover, use of ECLS/ECMO support during the acute phase of their illness appears rational (4).…”
mentioning
confidence: 99%